2002
DOI: 10.1530/eje.0.1460891
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and thyroxine during sexual development in male monkeys: effect of neonatal gonadotropin-releasing hormone antagonist treatment and delayed puberty on the developmental pattern of leptin and thyroxine secretion

Abstract: Objective: Neonatal treatment of male monkeys with a gonadotropin-releasing hormone antagonist (Ant) increased the incidence of delayed puberty. Using blood samples that had been collected from monkeys with normal or delayed puberty, we assessed the potential involvement of leptin and thyroxine (T4) in sexual development. Design and Methods: Monkeys were treated from birth until 4 months of age with vehicle, Ant or Ant/androgen and blood samples were drawn from 10 to 62 months of age. Results: Serum leptin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…Nevertheless, in primates the prepubertal increase in leptin does not stimulate the liberation of GnRH [33, 34] and, therefore, does not participate in the onset of puberty [35,36,37]. In humans leptin also plays an important role, since the ontogenic signals of the hypothalamic-pituitary-gonadal axis in the monkey and in man seem to be qualitatively identical [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in primates the prepubertal increase in leptin does not stimulate the liberation of GnRH [33, 34] and, therefore, does not participate in the onset of puberty [35,36,37]. In humans leptin also plays an important role, since the ontogenic signals of the hypothalamic-pituitary-gonadal axis in the monkey and in man seem to be qualitatively identical [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Although there were no observed changes in leptin levels prior to puberty, these data do not indicate whether differences in leptin levels between individuals account for some of the variation in the timing of puberty onset. In gonad-intact rhesus monkeys, leptin levels from 8–24 months and 26–50 months of age did not differ between males that reached puberty at 3.5 years of age and males that exhibited delayed puberty at 4.5 years of age, which suggests that variation in puberty timing is not influenced by leptin (Mann et al, 2002). Despite the relationship between body weight and puberty onset, the data indicate that leptin does not influence puberty onset in male rhesus macaques as leptin levels do not change around the time of puberty and differences in puberty timing are not the result of differences in leptin levels.…”
Section: Body Weight and Puberty Onsetmentioning
confidence: 95%
“…Intravenous GnRH administration increased LH levels comparably during both leptin or vehicle infusion, further supporting that exogenous leptin does not alter GnRH release or alter the timing of puberty onset (Barker-Gibb et al, 2002). Bimonthly endogenous leptin levels did not change during the year prior to puberty onset (26–38 months of age) or during puberty (39–50 months of age), and leptin levels remained constant even though increases in LH, T and testicular volume occurred between approximately 40–46 months of age in socially-housed male rhesus macaques living outdoors (Mann et al, 2000, 2002). Thus, there are no changes in endogenous leptin levels that seem to coincide with activation of the HPG axis and puberty onset.…”
Section: Body Weight and Puberty Onsetmentioning
confidence: 97%
See 1 more Smart Citation
“…Early studies showed that leptin accelerated puberty [22,48,49], suggesting that leptin might be a metabolic trigger for its time of onset. However, later studies did not report a good correlation between normal prepubertal serum leptin levels and the timing of puberty in normal rodents [50][51][52] or primates [53][54][55][56]. Therefore, Cheung et al [52], Urbanski [33], and Mann and Plant [32] suggested that leptin was not the trigger for puberty.…”
mentioning
confidence: 99%